Preparation method of double-drug-loaded ternary layered metal hydroxide nano treatment system
Through the dual drug-loaded ternary layered metal hydroxide nanotherapy system, the multimodal effects of Mn3+, Ga3+, DOX and ICG are used to solve the poor selectivity of existing anti-cancer treatment methods and the damage to normal cells, achieving efficient anti-tumor effects.
Patent Information
- Application Number
- CN202510079792.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-25
AI Technical Summary
The existing anti-cancer treatment methods have problems such as poor selectivity, high damage to normal cells, high risk of inducing gene mutations and high carcinogenic risk, and it is difficult to effectively eradicate tumors.
A dual-drug-loaded ternary layered metal hydroxide nanotherapy system is used to rapidly degrade in a weakly acidic tumor microenvironment and release Mn3+, Ga3+, DOX and ICG, using the anti-tumor activity and photothermal effects of these components to achieve multimodal combined treatment.
It significantly improves the killing effect on tumor cells, increases the reactive oxygen level in the cell, induces cancer cell death, and has a significant killing effect on tumors at a lower working concentration, while not affecting the survival of normal cells.
Smart Images

Figure CN119868581A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a dual-drug loaded ternary layered metal hydroxide nano therapeutic system, belonging to the technical field of biomedicine and health. Background Art
[0002] Cancer (malignant tumor) is a stubborn disease worldwide with high morbidity and mortality, and has become one of the three major life-threatening diseases. Therefore, it is particularly important to decide what method to use to treat tumors. Traditional treatments for tumors mainly include surgery, radiotherapy and chemotherapy. However, each of these three treatments has obvious defects in treating the disease. For example, surgical treatment cannot remove tiny residual lesions; postoperative trauma to the human body is large and prone to complications; radiotherapy can seriously damage the patient's own immune system, and the damage caused is difficult to repair by itself; although chemotherapy is a systemic treatment, it has poor drug selectivity, will kill a large number of normal cells, destroy the human immune system, and there is a risk of inducing gene mutations and carcinogenesis, providing the possibility for cancer cell recurrence and metastasis.
[0003] In recent years, targeting the unique tumor microenvironment (TME) of tumors, such as hypoxia, weak acidity, high hydrogen peroxide (H2O2) and high glutathione (GSH), some new cancer treatment methods, such as chemodynamic therapy (CDT), photothermal therapy (PTT), immunotherapy and starvation therapy, have been discovered. Chemodynamic therapy (CDT) mainly relies on variable-valence transition metal elements to trigger Fenton or Fenton-like reactions to convert high levels of hydrogen peroxide (H2O2) in tumor cells into hydroxyl radicals (·OH), causing tumor growth. DNA damage and proteins in tumor cells; Photothermal therapy (PTT) is a non-contact thermal therapy method. The basic principle is to use the photothermal effect to absorb light waves and convert them into heat under near-infrared light (NIR) irradiation, and induce thermal ablation of cells by increasing the temperature of the tumor tissue site; but in specific applications, it was found that the above single new treatment method is not enough to completely eradicate the tumor; At present, the widely recognized strategy is to combine the above emerging methods with chemotherapy, design an integrated system platform loaded with drugs on nanomaterials, and use multimodal combined therapy to enhance the killing effect on cancer cells and tumors.
[0004] In terms of materials, nano-layered double hydroxide is one of the preferred materials for drug loading. The nano-size ensures that the layered double hydroxide can be internalized by tumor cells and can produce effects inside and outside the cells (tumor microenvironment). Nano-sized materials have a high specific surface area. In addition, the layered double hydroxide has a layered structure inside, which can promote more drug small molecules to be inserted into the LDH interlayer under the effects of electrostatic adsorption and anion replacement, thereby further increasing the drug loading (loading capacity). More importantly, layered double hydroxide is unstable in the weakly acidic tumor microenvironment and is easily degraded to release a large number of metal ions. Among these metal ions, Mg 2+ , Mn 3+ , Ga 3+ It has certain anti-tumor activity; in terms of drugs, doxorubicin hydrochloride (DOX) is a typical broad-spectrum anti-tumor drug that can produce a wide range of biochemical effects on the body and is often used to treat acute myeloid leukemia, breast cancer, lung cancer, gastric cancer, liver cancer, etc. Indocyanine green (ICG) is currently the only near-infrared (NIR) fluorescent dye drug approved by the US FDA for clinical use, which can produce photothermal and photodynamic effects under near-infrared radiation. Summary of the invention
[0005] In view of the shortcomings of existing anticancer and antitumor treatments, the present invention discloses a method for preparing a dual-drug loaded ternary layered metal hydroxide nano-therapeutic system, which specifically comprises the following steps:
[0006] (1) Dissolving a Mg source, a Mn source and a Ga source in the same ultrapure water to prepare a solution I; dissolving a strong base, a metal nitrate or a metal carbonate in the same ultrapure water to prepare a solution II; adding the solution I dropwise to the solution II under heating conditions, stirring evenly, to obtain a solution III.
[0007] (2) The solution III obtained in step (1) is reacted at a temperature of 20 to 50° C. for 8 to 20 hours, during which the stirring speed of the mixed solution is 200 to 1000 r / min, to obtain a suspension I.
[0008] (3) The suspension I obtained in step (2) is centrifuged, then washed with ultrapure water, and dried under vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0009] (4) adding the MgMnGa-LDHs synthesized in step (3) into a phosphate buffer solution, and dispersing by ultrasonication to obtain suspension II; adding DOX (doxorubicin hydrochloride) and ICG (indocyanine green) into the phosphate buffer solution in sequence, and stirring by magnetic stirring to obtain solution IV.
[0010] (5) The suspension II and the solution IV are mixed and stirred evenly in the dark to obtain a solution V; the solution V is centrifuged, then washed with a phosphate buffer solution, and dried under vacuum at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system.
[0011] Preferably, the amount of Mg source added to solution I of step (1) is 0.1-5 g per 50-200 mL of ultrapure water; the amount of Mn source added to solution I is 0.03-3 g per 50-200 mL of ultrapure water; the amount of Ga source added to solution I is 0.05 g-4 g per 50-200 mL of ultrapure water; the Mg source, Mn source, and Ga source are their corresponding metal chlorides or metal nitrates.
[0012] Preferably, the amount of strong base added to solution II in step (1) is 0.1-15 g per 50-200 mL of ultrapure water; the strong base is NaOH or KOH; the amount of metal nitrate or metal carbonate in solution II is 0.2-25 g per 50-200 mL of ultrapure water, respectively, and the metal in the metal nitrate or metal carbonate is Na or K.
[0013] Preferably, in step (1), the volume ratio of solution I to solution II is (0.6-1.5):1.
[0014] Preferably, in step (1), the heating temperature is 20-70° C., the dripping speed of solution I to solution II is 0.5-2 s / drop, and the stirring speed is 100-500 r / min.
[0015] Preferably, the amount of MgMnGa-LDHs in suspension II of step (4) is 1 to 30 mg per 10 to 30 mL of phosphate buffer solution; the amount of DOX (doxorubicin hydrochloride) in solution IV is 5 to 100 mg per 10 to 30 mL of phosphate buffer solution; the amount of ICG (indocyanine green) in solution IV is 5 to 100 mg per 10 to 30 mL of phosphate buffer solution.
[0016] Preferably, the concentration of the phosphate buffer solution in step (4) is 0.1 mol / L, and the magnetic stirring time is 5 to 10 min.
[0017] Preferably, in step (5), the volume ratio of suspension II to solution IV is 1:(0.6-1.5).
[0018] Preferably, the temperature of the light-proof stirring in step (5) is 20-50° C., the time of the light-proof stirring is 8-48 h, and the speed of the light-proof stirring is 300-1000 r / min.
[0019] Technical effects of the present invention:
[0020] (1) The present invention provides a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs), which can be rapidly degraded in a weakly acidic tumor microenvironment to release Mn 3+ , Ga 3+ Active ions as well as DOX and ICG; among them, Mn 4+ / Mn 3+ / Mn 2+ The mutual redox reaction of Ga can catalyze the consumption of GSH and the conversion of H2O2, inducing cancer cell death by increasing the level of intracellular reactive oxygen species (ROS); 3+ Ions can kill cancer cells by inducing ferroptosis; DOX, as an anti-tumor drug, exerts its anti-cancer effect by inhibiting nucleic acid synthesis; ICG can increase the local temperature to above 45°C under 808nm near-infrared light irradiation, using the sensitivity of cancer cells to high temperatures to achieve a hyperthermia effect.
[0021] (2) This nanotherapy system effectively solves the problem of high GSH concentration in tumor cells and low Fenton-like reaction rate; under near-infrared light irradiation, the system accelerates the Mn 4+ / Mn 3+ / Mn 2+ It mediated a Fenton-like reaction and promoted the release of DOX, thereby significantly improving the effects of chemodynamic therapy and chemotherapy; ultimately, the system was able to have a significant killing effect on tumor cells at a lower working concentration without affecting the survival of normal cells, achieving a highly efficient anti-tumor effect.
[0022] (3) In the process of synthesizing MgMnGa-LDHs, the present invention regulates the morphology, size and relative molar percentage of Mn / Ga of nano-MgMnGa-LDHs by regulating parameters such as raw material type, dropwise addition speed, solution concentration, reaction temperature, time and stirring speed, so that the nano-MgMnGa-LDHs are microscopically lamellar with a size range of 20-180nm and an average size of 70nm; the molar fraction of Mn at the trivalent metal cation site is 57.44mol% to 73.55mol%, and the molar fraction of Ga is 26.45mol% to 42.56mol%.
[0023] (4) In the process of loading dual drugs on nanomaterials, the present invention regulates the drug loading rate (loading rate) by adjusting parameters such as the amount of nanomaterials and drugs, ultrasonic dispersion time and magnetic stirring time, temperature, time and stirring speed during light-proof mixing, so that DOX and ICG are loaded between the layers of MgMnGa-LDHs, and their loading rates (loading rates) are 110.33% to 166.56% and 147.08% to 213.28%, respectively.
[0024] (5) The DOX&ICG@MgMnGa-LDHs nanotherapeutic system of the present invention is pH responsive. Compared with the alkaline environment of pH 7.4, it can be rapidly degraded in the weakly acidic environment of pH 5.0 and pH 6.5. Especially under the condition of pH 6.5, Mn and Ga ions can be rapidly released within 45 minutes and tend to be stable after 2 hours.
[0025] (6) The DOX&ICG@MgMnGa-LDHs nanotherapy system of the present invention can consume glutathione (GSH), that is, decompose and release Mn 3+ The reduction reaction can consume more than 20% to 80% of GSH within 15 to 120 minutes; at the same time, its reduction product Mn 2+ / 3+ It can be further oxidized by H2O2 to generate hydroxyl radicals (·OH), and the amount of free radical production increases as the pH decreases from 7.4 to 5.0. As time goes by, the reduction of Mn by GSH combined with H2O2 oxidation can be achieved. 4+ / Mn 3+ / Mn 2+ The process of mutual transformation to generate hydroxyl radicals makes the DOX&ICG@MgMnGa-LDHs nanotherapeutic system exhibit chemodynamic therapy (CDT) characteristics.
[0026] (7) The DOX&ICG@MgMnGa-LDHs nanotherapy system of the present invention can generate heat by means of the photothermal effect of ICG, that is, in an acidic environment of pH 6.5, it is irradiated with 808nm near-infrared light for 5min to 10min, which can increase the temperature of the surrounding solution of the nanotherapy system with a concentration of 25μg / mL to 100μg / mL to 30-65°C, and after experiencing three cycles of "illumination for 5min-off for 5min", its temperature can still be maintained above 45°C, and the photothermal conversion efficiency (PCE) is above 30.47%. Considering that cancer cells cannot tolerate a higher extracellular microenvironment temperature, the light-induced temperature-raising behavior of the DOX&ICG@MgMnGa-LDHs nanotherapy system makes it exhibit photothermal therapy (PTT) characteristics.
[0027] (8) The DOX&ICG@MgMnGa-LDHs nanotherapeutic system of the present invention can decompose under acidic conditions, and the released DOX is a small drug molecule that can pass through the cancer cell membrane and directly act on its DNA structure; this drug behavior mode makes the DOX&ICG@MgMnGa-LDHs nanotherapeutic system exhibit chemotherapeutic (CT) characteristics.
[0028] (9) The DOX&ICG@MgMnGa-LDHs nanotherapeutic system of the present invention can be internalized by mouse breast cancer (4T1) cells due to its small size, and simultaneously produces reactive oxygen species in the cells to kill cancer cells, thereby achieving the purpose of anti-tumor.
[0029] (10) The DOX&ICG@MgMnGa-LDHs nanotherapeutic system of the present invention was co-cultured with mouse breast cancer (4T1) cells for 24 hours, causing the survival rate of 4T1 cells to drop to 36.16% to 20.36% at a concentration of 50 to 100 μg / mL; and was co-cultured with mouse fibroblasts (L929) for 24 hours, maintaining the survival rate of L929 cells above 73% at a concentration of 50 to 100 μg / mL.
[0030] (11) During the co-culture of the DOX&ICG@MgMnGa-LDHs nanotherapeutic system with mouse breast cancer (4T1) cells for 24 hours, 10 minutes of 808 nm near-infrared light irradiation was added. At a concentration of 50 to 100 μg / mL, the survival rate of 4T1 cells decreased from 36.16% to 24.11% without irradiation to 24.42% to 6.65% with irradiation. The nanotherapeutic system was degraded faster due to the increase in temperature. 3+ , Ga 3+ , DOX, and ICG are released in large quantities, which leads to synergistic enhancement of the four anticancer activity sources.
[0031] (12) The DOX&ICG@MgMnGa-LDHs nanotherapeutic system of the present invention has the characteristics of chemodynamic therapy (CDT), photothermal therapy (PTT) and chemotherapy (CT), and can implement multimodal combined treatment of tumors. Under the synergistic effect, the DOX&ICG@MgMnGa-LDHs nanotherapeutic system can kill cancer cells and achieve the purpose of anti-tumor at a working concentration of 50 to 100 μg / ml. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the X-ray diffraction (XRD) pattern of the product MgMnGa-LDHs in Example 1.
[0033] Figure 2 The transmission electron microscope (TEM) spectrum and particle size distribution diagram of the product MgMnGa-LDHs in Example 2 (a), the transmission electron microscope (TEM) spectrum of MgMnGa-LDHs and the element distribution energy spectrum diagram under full spectrum mode (mapping) (b).
[0034] Figure 3 This is the X-ray photoelectron spectrum (XPS) of the product MgMnGa-LDHs in Example 3.
[0035] Figure 4 This is the Fourier transform infrared spectrum (FTIR) of the product DOX&ICG@MgMnGa-LDHs in Example 4.
[0036] Figure 5 This is the ultraviolet-visible-near-infrared (UV-vis) absorption spectrum of DOX&ICG@MgMnGa-LDHs prepared in Example 5 (used to determine the drug loading).
[0037] Figure 6 Transmission electron microscopy (TEM) images of DOX&ICG@MgMnGa-LDHs prepared in Example 6 after being treated with PBS of different pH values (a) and ion release at different immersion times (b).
[0038] Figure 7 Ultraviolet-visible-near-infrared (UV-vis) spectra (a) of glutathione (GSH) consumption of DOX&ICG@MgMnGa-LDHs prepared in Example 7 at different treatment times under pH 6.5, and electroparamagnetic resonance (ESR) spectrum of DOX&ICG@MgMnGa-LDHs at pH 6.5 (b).
[0039] Figure 8 The DOX&ICG@MgMnGa-LDHs prepared in Example 8 were exposed to 808 nm laser (1 W / cm 2 ) Temperature rise curve under irradiation; (a) Cyclic photothermal heating-cooling curve; (b) is the "heating-cooling" curve of the cyclic test of "light irradiation for 5 min-off for 5 min" on 100 μg / mL DOX&ICG@MgMnGa-LDHs suspension.
[0040] Fig. 9 The DOX&ICG@MgMnGa-LDHs prepared in Example 9 were exposed to 808 nm laser (1 W / cm 2 ) UV-Vis-Near Infrared (UV-Vis) spectrum of drug small molecules released under irradiation.
[0041] Fig.10 CLSM image of cell uptake after co-culture of DOX&ICG@MgMnGa-LDHs prepared in Example 10 with 4T1 mouse breast cancer cells (a); CLSM image of ROS generation in 4T1 cells without treatment (b).
[0042] Fig.11 This is a cell viability diagram after co-culture of DOX&ICG@MgMnGa-LDHs prepared in Example 11 with L929 mouse fibroblasts and 4T1 mouse breast cancer cells.
[0043] Fig.12 This is a cell viability diagram of the DOX&ICG@MgMnGa-LDHs prepared in Example 12 after co-culture with 4T1 mouse breast cancer cells with and without NIR treatment. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0045] Example 1
[0046] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0047] (1) Dissolve 5 g of MgCl2·6H2O, 3 g of MnCl2, and 4 g of GaCl3 in 200 ml of ultrapure water to prepare solution I; dissolve 15 g of NaOH and 25 g of NaNO3 in 200 ml of ultrapure water to prepare solution II; gradually add solution I to solution II that is being heated and stirred at a rate of 0.5 s / drop to obtain solution III. The heating temperature is 20°C and the stirring speed is set to 500 r / min.
[0048] (2) The solution III obtained in step (1) was stirred at a speed of 1000 r / min and the mixture was placed at 50° C. for 8 h to obtain a suspension I.
[0049] (3) The suspension I obtained in step (2) was centrifuged (8000 r / min, 5 min), the obtained precipitate was washed with ultrapure water, and vacuum dried at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0050] (4) 1 mg of the synthesized MgMnGa-LDHs was added to 30 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 5 min to prepare suspension II; 5 mg of DOX and 5 mg of ICG were added to 30 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 5 min to prepare solution IV.
[0051] (5) The suspension II and the solution IV were mixed, and stirred continuously at 300 r / min for 48 h at a temperature of 20°C in the dark; the resulting mixture was centrifuged (10000 r / min, 5 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0052] In this example, ternary layered metal hydroxide MgMnGa-LDHs was prepared and its phase was characterized by X-ray diffractometer (XRD). The results are as follows: Figure 1 As shown in the figure, it can be seen that the diffraction peak position of the product MgMnGa-LDHs corresponds to the diffraction peak position of the standard card #44-1446, which proves that the synthesized product is a layered double hydroxide (commonly known as hydrotalcite, a typical representative is montmorillonite). In addition, the diffraction peaks located at the diffraction angle (2θ) of 59.39° and 60.72°, respectively belonging to the (110) and (113) crystal planes, are "splitting peaks" unique to layered double hydroxides. The above two diffraction peaks of the product of this embodiment are relatively independent of each other, proving that the mixing of the upper layer and the interlayer of the MgMnGa-LDHs crystal structure is low, and the interlayer integrity is good.
[0053] Example 2
[0054] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0055] (1) Dissolve 0.1 g of Mg(NO3)2·6H2O, 0.03 g of Mn(NO3)2·4H2O and 0.05 g of Ga(NO3)3·xH2O in 50 ml of ultrapure water to prepare solution I. Dissolve 0.1 g of KOH and 0.2 g of K2CO3 in 50 ml of ultrapure water to prepare solution II. Add solution I gradually dropwise to solution II which is being heated and stirred at a rate of 2 s / drop to obtain solution III. The heating temperature is 70°C and the stirring speed is set to 100 r / min.
[0056] (2) The solution III obtained in step (1) was stirred at a speed of 200 r / min and the mixture was placed at 20° C. for reaction for 20 h to obtain a suspension I.
[0057] (3) The suspension I obtained in step (2) was centrifuged (6000 r / min, 6 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0058] (4) 1 mg of the synthesized MgMnGa-LDHs was added to 10 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 10 min to prepare suspension II; 100 mg of DOX and 100 mg of ICG were added to 10 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 10 min to prepare solution IV.
[0059] (5) The suspension II and the solution IV were mixed, and stirred continuously at 1000 r / min for 8 h at a temperature of 50°C in the dark; the resulting mixture was centrifuged (6000 r / min, 10 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0060] In this example, ternary layered metal hydroxide MgMnGa-LDHs was prepared, and its morphology and element distribution were characterized by transmission electron microscopy (TEM) combined with energy dispersive X-ray detection (EDX). The results are as follows: Figure 2 As shown by Figure 2 (a) It can be seen that MgMnGa-LDHs are lamellar nanoparticles. The size of more than 30 particles was measured and counted, and it was found that the size of MgMnGa-LDHs was normally distributed, ranging from 40 to 110 nm, with an average size of 78.6±16.1 nm, which can ensure that it can be phagocytosed by cancer (tumor) cells. Figure 2 (b) It can be seen that Mg, Mn and Ga can be detected in a single nanoparticle in the full spectrum scanning (mapping) mode, further confirming that MgMnGa-LDHs is a ternary layered metal hydroxide. In addition, Mg, Mn and Ga are bright in color and can be evenly distributed throughout the nanoparticle, which potentially indicates that the content of the three elements is high enough and there is no composition segregation.
[0061] Example 3
[0062] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0063] (1) 0.813 g of MgCl2·6H2O, 0.252 g of MnCl2 and 0.264 g of GaCl3 were dissolved in 100 ml of ultrapure water to prepare solution I; 1.6 g of NaOH and 2.65 g of Na2CO3 were dissolved in 100 ml of ultrapure water to prepare solution II; solution I was gradually added dropwise to solution II which was being heated and stirred at a rate of 0.5 s / drop to obtain solution III. The heating temperature was 30°C and the stirring speed was set to 500 r / min.
[0064] (2) The solution III obtained in step (1) was stirred at a speed of 400 r / min and the mixture was reacted at 20° C. for 8 h to obtain a suspension I.
[0065] (3) The suspension I obtained in step (2) was centrifuged (8000 r / min, 5 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0066] (4) 20 mg of the synthesized MgMnGa-LDHs was added to 30 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 5 min to prepare suspension II; 70 mg of DOX and 70 mg of ICG were added to 30 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 5 min to prepare solution IV.
[0067] (5) The suspension II and the solution IV were mixed, and stirred continuously at 500 r / min for 48 h at 25°C in the dark; the resulting mixture was centrifuged (8000 r / min, 15 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0068] In this example, ternary layered metal hydroxide MgMnGa-LDHs was prepared, and its elemental valence state was characterized by X-ray photoelectron spectroscopy (XPS). The results are as follows: Figure 3 As shown in the figure, Mn 2p is further divided into two characteristic peaks, Mn 2p3 / 2 and Mn 2p1 / 2, in the XPS spectrum. The corresponding binding energies of the two peaks are close to Mn 3+ The standard values of 641.4eV and 653.3eV; similarly, the binding energies of the Ga 2p3 / 2 and Ga 2p1 / 2 characteristic peaks split from Ga 2p are also close to those of Ga 3+ The standard values are 1118.0eV and 1145.0eV, which confirms that Mn and Ga in the MgMnGa-LDHs product are both +3 valence, and jointly occupy the trivalent metal cation site on the LDHs lattice. Further, 1g of nano-MgMnGa-LDHs was completely dissolved in dilute hydrochloric acid, and then tested by inductively coupled plasma mass spectrometry (ICP / MS). The mass fractions of the measured elements Mg, Mn, and Ga were 15.76ωt%, 17.33ωt%, and 10.08ωt%, respectively. It can be calculated that the molar fraction of Mn in the trivalent metal cation site is 68.56mol%, and the molar fraction of Ga in the trivalent metal cation site is 31.43mol%.
[0069] Example 4
[0070] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0071] (1) Dissolve 0.610 g of Mg(NO3)2·6H2O, 0.101 g of Mn(NO3)2·4H2O and 0.317 g of Ga(NO3)3·xH2O in 50 ml of ultrapure water to prepare solution I. Dissolve 1 g of KOH and 2.2 g of KNO3 in 50 ml of ultrapure water to prepare solution II. Add solution I dropwise to solution II which is being heated and stirred at a rate of 1 s / drop to obtain solution III. The heating temperature is 50°C and the stirring speed is set to 100 r / min.
[0072] (2) The solution III obtained in step (1) was stirred at a speed of 200 r / min and the mixture was placed at 30° C. for 20 h to obtain a suspension I.
[0073] (3) The suspension I obtained in step (2) was centrifuged (10000 r / min, 5 min), the obtained precipitate was washed with ultrapure water, and vacuum dried at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0074] (4) 4 mg of the synthesized MgMnGa-LDHs was added to 10 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 10 min to prepare suspension II; 30 mg of DOX and 30 mg of ICG were added to 10 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 10 min to prepare solution IV.
[0075] (5) The suspension II and the solution IV were mixed, and stirred continuously at 1000 r / min for 8 h at 40°C in the dark; the resulting mixture was centrifuged (10000 r / min, 6 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0076] The structures of the two drug raw materials DOX and ICG, the synthesized nano-MgMnGa-LDHs, and the DOX&ICG@MgMnGa-LDHs nano-therapeutic system used in this example were characterized by Fourier transform infrared spectroscopy (FTIR). The results are shown in FIG. Figure 4As shown in the figure, DOX and ICG, as small organic molecules, show several characteristic absorption peaks in the FTIR spectrum; while nano-MgMnGa-LDHs has no corresponding characteristic absorption at the same wave number. It can be inferred that DOX&ICG@MgMnGa-LDHs has characteristic absorption at specific wave numbers, especially at 1286cm -1 and 1090cm -1 The absorption peaks at and come from DOX and ICG, respectively, which indicates that the two drug molecules have been successfully loaded on the nano-MgMnGa-LDHs carrier through electrostatic adsorption, anion replacement and other effects.
[0077] Example 5
[0078] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0079] (1) Dissolve 2.5 g of Mg(NO3)2·6H2O, 1.5 g of Mn(NO3)2·4H2O and 2 g of Ga(NO3)3·xH2O in 100 ml of ultrapure water to prepare solution I. Dissolve 7.5 g of NaOH and 12.5 g of Na2CO3 in 100 ml of ultrapure water to prepare solution II. Add solution I gradually dropwise to solution II which is being heated and stirred at a rate of 1 s / drop to obtain solution III. The heating temperature is 45°C and the stirring speed is set to 300 r / min.
[0080] (2) The solution III obtained in step (1) was stirred at a speed of 600 r / min and the mixture was placed at 35° C. for 14 h to obtain a suspension I.
[0081] (3) The suspension I obtained in step (2) was centrifuged (8000 r / min, 5 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0082] (4) 25 mg of the synthesized MgMnGa-LDHs was added to 15 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 10 min to prepare suspension II; 15 mg of DOX and 15 mg of ICG were added to 20 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 6 min to prepare solution IV.
[0083] (5) The suspension II and the solution IV were mixed, and stirred continuously at 700 r / min for 14 h at 25°C in the dark; the resulting mixture was centrifuged (8000 r / min, 15 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0084] The two drug raw materials DOX and ICG used in this example and the synthesized DOX&ICG@MgMnGa-LDHs nano-therapeutic system were weighed 50 mg respectively and dispersed in 10 ml of 0.1 mol / L PBS buffer to prepare a dispersion. The characteristic absorption of the dispersion was characterized by UV-Vis near-infrared spectrophotometer (UV-Vis). The results are shown in FIG. Figure 5 As shown in the figure, it can be seen that according to the figure, the two drug small molecules DOX and ICG have characteristic absorption peaks centered at wavelengths of 480nm and 778nm, respectively. Similarly, characteristic absorption peaks also appear in the DOX&ICG@MgMnGa-LDHs nanotherapy system, with their centers located at 490nm and 842nm. By comparison, it can be confirmed that the characteristic absorption peaks in the nanotherapy system originate from DOX and ICG, but after electrostatic adsorption, anion replacement and other interactions with MgMnGa-LDHs, the peak center shifts. This result further confirms that DOX and ICG have been successfully loaded on the nano MgMnGa-LDHs carrier. Further, the absorbance-concentration characteristic equation of DOX Y(absorbance) = 0.0154×X(drug concentration) + 0.0066, the absorbance-concentration characteristic equation of ICG Y(absorbance) = 0.0316×X(drug concentration) -0.003 and the loading rate calculation formula LC (装载率) = drug loading amount (g) / total product amount (g), it can be seen that the loading rates (loading rates) of DOX and ICG in DOX&ICG@MgMnGa-LDHs are 166.52% and 141.36%, respectively.
[0085] Example 6
[0086] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0087] (1) 1.25 g of MgCl2·6H2O, 0.75 g of MnCl2 and 1 g of GaCl3 were dissolved in 150 ml of ultrapure water to prepare solution I; 3.75 g of KOH and 6.25 g of NaNO3 were dissolved in 100 ml of ultrapure water to prepare solution II; solution I was gradually added dropwise to solution II which was being heated and stirred at a rate of 1.5 s / drop to obtain solution III. The heating temperature was 40°C and the stirring speed was set to 300 r / min.
[0088] (2) The solution III obtained in step (1) was stirred at a speed of 300 r / min and the mixture was placed at 25° C. for 16 hours to obtain a suspension I.
[0089] (3) The suspension I obtained in step (2) was centrifuged (9000 r / min, 6 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0090] (4) 10 mg of the synthesized MgMnGa-LDHs was added to 25 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 8 min to prepare suspension II; 60 mg of DOX and 40 mg of ICG were added to 25 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 8 min to prepare solution IV.
[0091] (5) The suspension II and the solution IV were mixed, and stirred continuously at 400 r / min for 30 h at 35°C in the dark; the resulting mixture was centrifuged (9000 r / min, 8 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0092] In this embodiment, a DOX&ICG@MgMnGa-LDHs nano-therapeutic system was prepared, and equal amounts of the system were respectively placed in 10 ml of PBS buffer solution with a pH of 5.0, 6.5, and 7.4 and a concentration of 0.1 mol / L. After standing for 2 hours, the system was centrifuged, and the nano-therapeutic system soaked in PBS was vacuum dried, and its microscopic morphology was characterized by transmission electron microscopy (TEM). The results are shown in FIG. Figure 6As shown in (a), it can be seen from the figure that DOX&ICG@MgMnGa-LDHs show obvious differences in stability in immersion solutions with different pH values. In the weakly alkaline environment of pH 7.4, the main body of MgMnGa-LDHs maintains its lamellar characteristics, and the overall morphology is regular, and no structural collapse is observed at the edge. On the contrary, under the acidic conditions of pH 6.5 and pH 5.0, the unique lamellar morphology of MgMnGa-LDHs almost completely disappears, and as the pH value decreases, this phenomenon becomes more obvious; especially at pH 5.0, the main body of MgMnGa-LDHs has become irregular fragmented sheets superimposed on each other. In addition, under the immersion condition of pH 6.5, the acidic environment has a negative effect on the hydroxide product. The corrosion causes its structure to collapse and causes the loaded small molecule drugs (small black or gray dots with a diameter of less than 5 nm in the figure) to be released into the solution. In view of the difference in structural stability in the above acidic and alkaline environments, it can be determined that the DOX&ICG@MgMnGa-LDHs product has pH response characteristics. Similarly, an equal amount of DOX&ICG@MgMnGa-LDHs nanotherapy system was put into 10 ml of PBS buffer with a pH of 6.5 and a concentration of 0.1 mol / L. After standing for a certain period of time, the separated clear liquid was filtered with a 0.22 μm filter membrane, and the release amount of Mn and Ga in the clear liquid (mg / L) was tested by inductively coupled plasma mass spectrometry (ICP-MS). The results are shown in Figure 2. Figure 6 As shown in (b), it can be seen from the figure that Mn and Ga are released into the solution due to the structural collapse of nano-MgMnGa-LDHs in an acidic environment. The release amounts of both show a rapid and then stable change trend with the extension of immersion time. Specifically, Mn 3+ The rapid release is completed within 1 hour and turns to steady release within 4 to 12 hours; while Ga 3+ The rapid release was completed within 0.75 hours and turned into a steady release within 4 to 12 hours. 3+ The release amount at any time point was higher than that of Mn 3+ .
[0093] Example 7
[0094] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0095] (1) Dissolve 1 g of MgCl2·6H2O, 0.6 g of MnCl2, and 0.8 g of GaCl3 in 75 ml of ultrapure water to prepare solution I; dissolve 3 g of NaOH and 5 g of KNO3 in 75 ml of ultrapure water to prepare solution II; gradually add solution I to solution II that is being heated and stirred at a rate of 1.5 s / drop to obtain solution III. The heating temperature is 30°C and the stirring speed is set to 2500 r / min.
[0096] (2) The solution III obtained in step (1) was stirred at a speed of 400 r / min and the mixture was placed at 30° C. for 12 h to obtain a suspension I.
[0097] (3) The suspension I obtained in step (2) was centrifuged (12000 / min, 5 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0098] (4) 25 mg of the synthesized MgMnGa-LDHs was added to 25 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 6 min to prepare suspension II; 80 mg of DOX and 80 mg of ICG were added to 15 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 10 min to prepare solution IV.
[0099] (5) The suspension II and the solution IV were mixed, and stirred continuously at 600 r / min for 10 h at a temperature of 45°C in the dark; the resulting mixture was centrifuged (8000 r / min, 5 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0100] In this embodiment, a DOX&ICG@MgMnGa-LDHs nanotherapy system was prepared, which was added to 0.1 mol / L PBS to prepare a suspension with a concentration of 1 mg / mL. GSH and DTNB were dissolved in 0.1 mol / L PBS to prepare a 5 mmol / L GSH solution and a 1 mg / ml DTNB solution. 400 μL of the suspension and 400 μL of the GSH solution were mixed, and 800 μL of the mixed solution was added to a 5 mL, pH 6.5, 0.1 mol / L PBS solution. l / L PBS buffer solution for reaction at 0min, 15min, 30min, 45min, 60min and 120min respectively; then 200μL DTNB solution was added, and the characteristic absorption of the above-mentioned final mixed solution was characterized by ultraviolet-visible near-infrared spectrophotometer (UV-Vis). The GSH depletion ability of DOX&ICG@MgMnGa-LDHs nanotherapy system was evaluated by analyzing the changes in the characteristic absorption peak intensity (absorbance) at different reaction times. The results are shown in Figure 7 As shown in (a), since GSH itself has no UV absorption, its detection needs to be investigated after GSH depletion is completed by adding another DTNB without UV absorption to promote the reaction of residual GSH with DTNB to generate TNB. As can be seen from the figure, the characteristic absorption peak of TNB product appears at 412nm in the final mixed solution, and with the extension of reaction time, the absorbance of TNB gradually decreases, indicating that the residual amount of GSH is constantly decreasing, further indicating that more GSH in the original solution is consumed by DOX&ICG@MgMnGa-LDHs. The specific consumption mechanism is that in the acidic environment of pH 6.5, the structure of MgMnGa-LDHs collapses and the released Mn 3+ ions are reduced to Mn 2+ ions, and GSH was oxidized to GSSG. The absorbance of TNB was used to reversely calculate that the consumption rate of GSH by DOX&ICG@MgMnGa-LDHs nanotherapy system was 22.7% and 82.4% at 15min and 120min, respectively. Further, 10mg of DOX&ICG@MgMnGa-LDHs, 10mg of GSH and 1mL of 30% H2O2 were weighed and added into a PBS buffer solution with a pH of 6.5, a volume of 10mL and a concentration of 0.1mol / L to prepare a mixed solution. After the mixed solution was reacted for 10min by using an ESR / EPR spectrometer, whether free radicals were generated after the reaction of DOX&ICG@MgMnGa-LDHs with GSH and H2O2 in the above system and the types of free radicals were characterized. The results are shown in Figure 7As shown in (b), compared with the case where only GSH and H2O2 exist, it is confirmed that DOX&ICG@MgMnGa-LDHs triggers the reaction to generate free radicals, and according to the characteristics of the signal 1:2:2:1, it is further determined to be hydroxyl radicals (·OH). Its generation mechanism is that Mn generated by GSH reduction 2+ ions and unreacted Mn 3+ ions can be further oxidized by H2O2, triggering the Mn 2+ (Mn 3+ )+H2O2→Mn 3+ (Mn 4+ )+·OH+OH - Fenton-like reaction, Mn 4+ / Mn 3+ / Mn 2+ The redox activity enables the DOX&ICG@MgMnGa-LDHs nanotherapeutic system to catalyze the conversion of high concentrations of GSH and H2O2 in cancer (tumor) cells into GSSG and ·OH, exhibiting chemodynamic therapy (CDT) properties.
[0101] Example 8
[0102] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0103] (1) Dissolve 1 g of Mg(NO3)2·6H2O, 0.6 g of Mn(NO3)2·4H2O and 0.8 g of Ga(NO3)3·xH2O in 125 ml of ultrapure water to prepare solution I. Dissolve 3 g of NaOH and 5 g of K2CO3 in 100 ml of ultrapure water to prepare solution II. Add solution I dropwise to solution II which is being heated and stirred at a rate of 1.5 s / drop to obtain solution III. The heating temperature is 55°C and the stirring speed is set to 150 r / min.
[0104] (2) The solution III obtained in step (1) was stirred at a speed of 700 r / min and the mixture was placed at 45° C. for 10 h to obtain a suspension I.
[0105] (3) The suspension I obtained in step (2) was centrifuged (10000 r / min, 8 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0106] (4) 5 mg of the synthesized MgMnGa-LDHs was added to 12 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 7 min to prepare suspension II; 75 mg of DOX and 75 mg of ICG were added to 18 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 10 min to prepare solution IV.
[0107] (5) The suspension II and the solution IV were mixed, and stirred continuously at 800 r / min for 40 h at 25°C in the dark; the resulting mixture was centrifuged (8000 r / min, 20 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0108] In this embodiment, a DOX&ICG@MgMnGa-LDHs nanotherapy system was prepared, which was added to PBS with a pH of 6.5 and a concentration of 0.1 mol / L to prepare suspensions with concentrations of 100 μg / mL, 75 μg / mL, 50 μg / mL, and 25 μg / mL, respectively. 0.35 ml of the suspensions of each concentration was taken and the wavelength was 808 nm and the power density was 1 W / cm 2 The near-infrared light was irradiated for 5 minutes, during which the temperature rise of the suspension was recorded using a thermocouple thermometer. The results are shown in Figure 8 As shown in (a), it can be seen from the figure that the amount of ICG loaded by DOX&ICG@MgMnGa-LDHs increases with the continuous increase of the concentration of the suspension. ICG generates heat under near-infrared light, causing the temperature of the entire suspension system to rise. When the concentration is 100μg / mL, the maximum temperature can reach 45.7±1.1℃. When the DOX&ICG@MgMnGa-LDHs nanotherapy system transfers heat to the surrounding area to make its temperature meet 42~50℃, it can cause thermal damage to the tumor site and kill cancer (tumor) cells by destroying the integrity and permeability of the cell membrane, showing photothermal therapy characteristics (PTT). Furthermore, using near-infrared light of the same wavelength and power density, a 100μg / mL DOX&ICG@MgMnGa-LDHs suspension was subjected to a "light irradiation 5min-off 5min" cycle test. Its "heating-cooling" curve is shown in Figure 8 As shown in (b), it can be seen from the figure that after 3 cycles, the maximum temperature of DOX&ICG@MgMnGa-LDHs changed from 50.9°C to 47.2°C, maintaining good stability. Based on the above results, it can be calculated that the photothermal conversion efficiency (PCE) of the DOX&ICG@MgMnGa-LDHs nanotherapy system is 31.26%.
[0109] Example 9
[0110] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0111] (1) Dissolve 2.5 g of MgCl2·6H2O, 1.2 g of MnCl2 and 2 g of GaCl3 in 140 ml of ultrapure water to prepare solution I; dissolve 7.5 g of NaOH and 12.5 g of KNO3 in 140 ml of ultrapure water to prepare solution II; gradually add solution I to solution II which is being heated and stirred at a rate of 0.5 s / drop to obtain solution III. The heating temperature is 35°C and the stirring speed is set to 400 r / min.
[0112] (2) The solution III obtained in step (1) was stirred at a speed of 400 r / min and the mixture was placed at 35° C. for 15 hours to obtain a suspension I.
[0113] (3) The suspension I obtained in step (2) was centrifuged (6000 r / min, 10 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0114] (4) 22 mg of the synthesized MgMnGa-LDHs was added to 14 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 8 min to prepare suspension II; 85 mg of DOX and 75 mg of ICG were added to 14 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 10 min to prepare solution IV.
[0115] (5) The suspension II and the solution IV were mixed, and stirred continuously at 750 r / min for 26 h at a temperature of 30°C in the dark; the resulting mixture was centrifuged (10000 r / min, 10 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0116] The DOX&ICG@MgMnGa-LDHs nanotherapeutic system prepared in this example was added to PBS with a pH of 6.5 and a concentration of 0.1 mol / L to prepare a suspension with a concentration of 100 μg / mL. 2 The suspension was irradiated with near-infrared light for 0 to 30 minutes, and the characteristic absorption of the suspension was characterized by an ultraviolet-visible near-infrared (UV-Vis) spectrophotometer. Fig. 9As shown in the figure, it can be seen that the suspension has characteristic absorption peaks of DOX and ICG at 480nm and 780nm, respectively, and the peak positions of the two absorption peaks are close to the standard peak positions of ultraviolet absorption of the two drug small molecules, indicating that the two characteristic peaks originate from DOX and ICG released by DOX&ICG@MgMnGa-LDHs. With the extension of illumination time, the absorbance of DOX and ICG gradually increases, indicating that more drug small molecules are released into the solution. Based on the results shown in Example 8, DOX&ICG@MgMnGa-LDHs has photothermal properties and can accelerate the structural disintegration of MgMnGa-LDHs by heating in a weakly acidic environment of pH 6.5, thereby promoting drug release. In general, the light-induced heating behavior of DOX&ICG@MgMnGa-LDHs not only enhances drug release, but also accelerates carrier decomposition, increases the concentration of variable-valence metal Mn, and thereby enhances the relevant performance of chemodynamic therapy and chemotherapy.
[0117] Example 10
[0118] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0119] (1) Dissolve 3.75 g of Mg(NO3)2·6H2O, 2.25 g of Mn(NO3)2·4H2O and 3 g of Ga(NO3)3·xH2O in 180 ml of ultrapure water to prepare solution I. Dissolve 11.25 g of NaOH and 18.75 g of NaNO3 in 120 ml of ultrapure water to prepare solution II. Add solution I dropwise to solution II which is being heated and stirred at a rate of 1 s / drop to obtain solution III. The heating temperature is 30°C and the stirring speed is set to 150 r / min.
[0120] (2) The solution III obtained in step (1) was stirred at a speed of 450 r / min and the mixture was placed at 50° C. for reaction for 12 h to obtain a suspension I.
[0121] (3) The suspension I obtained in step (2) was centrifuged (8000 r / min, 6 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0122] (4) 17 mg of the synthesized MgMnGa-LDHs was added to 17 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 6 min to prepare suspension II; 25 mg of DOX and 45 mg of ICG were added to 17 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 10 min to prepare solution IV.
[0123] (5) The suspension II and the solution IV were mixed, and stirred continuously at 400 r / min for 17 h at 35°C in the dark; the resulting mixture was centrifuged (10000 r / min, 10 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0124] The DOX&ICG@MgMnGa-LDHs nanotherapy system prepared in this embodiment was sterilized by high-temperature and high-pressure steam at 121°C for 20 min in advance, and then a complete culture medium was added to prepare a 50 μg / mL sample solution. The sample solution was mixed with mouse breast cancer cells (4T1), and co-cultured in a 5% CO2, 37°C constant temperature incubator for 12 h. The cells were washed with PBS to remove excess serum, and stained with 5 μg / mL DAPI for 10 min. The stained cells were placed under a laser confocal microscope (CLSM) to observe whether the DOX&ICG@MgMnGa-LDHs nanotherapy system can be internalized by the cells. The results are shown in FIG. Fig.10 As shown in (a), it can be seen from the figure that DOX does not show color in the blank control group without sample under the excitation wavelength of 559nm, but shows red light with an emission wavelength of 619nm in the sample group, so the red light spot is DOX. Similarly, DAPI can show blue light with an emission wavelength of 619nm in both the blank control group and the sample group under the excitation wavelength of 559nm. DAPI can only stain the nucleus of 4T1 cells, so the blue light spot is the nucleus. It can be further obtained that DOX can be observed around the nucleus in the sample group on the Merge graph, and the content is relatively high, which confirms that DOX&ICG@MgMnGa-LDHs has been internalized by the cells and ICG, DOX and Mn are released in the cells. 3+ , Ga 3+ ions to achieve anti-tumor multimodal combined therapy. Similarly, the sample solution and mouse breast cancer 4T1 cells were co-cultured for 24 hours according to the same parameters and operations. After PBS washing to remove excess serum, the cells were stained with diluted DCFH-DA staining solution at 37°C for 30 minutes in the dark, and then the level of reactive oxygen species (ROS) in 4T1 cells was observed under a laser confocal microscope (CLSM). The results are shown in Figure 2. Fig.10 As shown in (b), the blank control group without sample does not show color, while the sample group emits green light. The DCFH-DA dye needs the active oxygen in the cell to activate the light. Therefore, it can be determined that DOX&ICG@MgMnGa-LDHs can significantly increase the ROS level in the cell. Fig.10The results of (a) and (b) show that the DOX&ICG@MgMnGa-LDHs nanotherapeutic system can be internalized by cancer (tumor) cells and accumulate sufficient free radicals in the cells to effectively kill the tumor from the inside.
[0125] Embodiment 11
[0126] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0127] (1) Dissolve 1.5 g of Mg(NO3)2·6H2O, 0.9 g of Mn(NO3)2·4H2O and 1.2 g of Ga(NO3)3·xH2O in 72 ml of ultrapure water to prepare solution I. Dissolve 4.5 g of KOH and 7.5 g of KNO3 in 120 ml of ultrapure water to prepare solution II. Add solution I gradually dropwise to solution II which is being heated and stirred at a rate of 1 s / drop to obtain solution III. The heating temperature is 60°C and the stirring speed is set to 400 r / min.
[0128] (2) The solution III obtained in step (1) was stirred at a speed of 700 r / min and the mixture was placed at 35° C. for 18 hours to obtain a suspension I.
[0129] (3) The suspension I obtained in step (2) was centrifuged (8000 r / min, 6 min), and the obtained precipitate was washed with ultrapure water and dried in vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0130] (4) 20 mg of the synthesized MgMnGa-LDHs was added to 20 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 9 min to prepare suspension II; 55 mg of DOX and 75 mg of ICG were added to 18 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 9 min to prepare solution IV.
[0131] (5) The suspension II and the solution IV were mixed, and stirred continuously at 550 r / min for 28 h at a temperature of 42°C in the dark; the resulting mixture was centrifuged (6000 r / min, 20 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0132] In this embodiment, a DOX&ICG@MgMnGa-LDHs nanotherapy system was prepared, which was sterilized by high-temperature and high-pressure steam at 121°C for 20 min in advance, and then added to a complete culture medium to prepare a suspension with a concentration of 1 mg / mL and ultrasonicated for 10 min to disperse it evenly. The complete culture medium was used to dilute it again to reduce the concentration to 6.25 μg / mL, 12.5 μg / mL, 25 μg / mL, 50 μg / mL and 100 μg / mL, respectively. The diluted sample suspension was mixed with mouse breast cancer cells (4T1) and mouse fibroblasts (L929), respectively, and co-cultured in a 5% CO2, 37°C constant temperature incubator for 24 h. After the culture was completed, excess serum was removed with PBS, and 10% CCK-8 indicator was added. The system was kept in the dark for 2 h under the same conditions, and the absorbance of the sample at 450 nm was measured with an enzyme marker and the relative cell viability was calculated. The results are shown in FIG. Fig.11 As shown in the figure, it can be seen that with the increase of working concentration, the cell viability of L929 cells and 4T1 cells shows a downward trend, and the viability of 4T1 cancer cells is significantly lower than that of L929 cells at the same working concentration. Moreover, in the working concentration range of 50-100 μg / mL, the DOX&ICG@MgMnGa-LDHs nanotherapy system can cause more than 65% of 4T1 cell death, and does not reduce the viability of L929 cells to below 70 to produce cytotoxicity. This further shows that the DOX&ICG@MgMnGa-LDHs nanotherapy system has obvious targeting and can effectively kill cancer cells without causing negative impact on the survival of normal cells.
[0133] Example 12
[0134] A dual drug loaded ternary layered metal hydroxide (DOX&ICG@MgMnGa-LDHs) nanotherapeutic system was prepared, and the specific steps are as follows:
[0135] (1) Dissolve 2.25 g of Mg(NO3)2·6H2O, 1.35 g of Mn(NO3)2·4H2O and 1.8 g of Ga(NO3)3·xH2O in 110 ml of ultrapure water to prepare solution I. Dissolve 6.75 g of NaOH and 11.25 g of NaNO3 in 180 ml of ultrapure water to prepare solution II. Add solution I dropwise to solution II which is being heated and stirred at a rate of 0.5 s / drop to obtain solution III. The heating temperature is 55°C and the stirring speed is set to 350 r / min.
[0136] (2) The solution III obtained in step (1) was stirred at a speed of 550 r / min and the mixture was reacted at 30° C. for 16 h to obtain a suspension I.
[0137] (3) The suspension I obtained in step (2) was centrifuged (10000 r / min, 5 min), the obtained precipitate was washed with ultrapure water, and vacuum dried at room temperature to obtain a dark brown MgMnGa-LDHs product.
[0138] (4) 30 mg of the synthesized MgMnGa-LDHs was added to 12 ml of 0.1 mol / L phosphate buffer solution (PBS) and ultrasonically dispersed for 10 min to prepare suspension II; 95 mg of DOX and 75 mg of ICG were added to 10 ml of 0.1 mol / L phosphate buffer solution (PBS) in sequence and magnetically stirred for 9 min to prepare solution IV.
[0139] (5) The suspension II and the solution IV were mixed, and stirred continuously at 550 r / min for 28 h at a temperature of 42°C in the dark; the resulting mixture was centrifuged (10000 r / min, 5 min), the precipitate was washed with PBS, and vacuum dried at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system (DOX&ICG@MgMnGa-LDHs nanotherapeutic system).
[0140] In this embodiment, the DOX&ICG@MgMnGa-LDHs nanotherapy system was prepared, and it was sterilized by high temperature and high pressure steam at 121°C for 20 min in advance; then it was added to the complete culture medium to prepare a suspension with a concentration of 1 mg / mL and ultrasonicated for 10 min to disperse it evenly, and then it was diluted again with the complete culture medium to reduce the concentration to 6.25μg / mL, 12.5μg / mL, 25μg / mL, 50μg / mL and 100μg / mL, respectively, and the diluted samples were suspended The solution was divided into two groups, A and B, according to the same concentration, and mixed with mouse breast cancer cells (4T1) respectively, and co-cultured in a 5% CO2, 37°C constant temperature incubator for 24 hours. During this period, group A was not treated with near-infrared light in the middle, and group B was irradiated with 808nm near-infrared light for 10 minutes after 12 hours. After the culture was completed, excess serum was removed with PBS, and 10% CCK-8 indicator was added. The samples were kept in the dark for 2 hours under the same conditions, and the absorbance value of the samples at 450nm was measured with an enzyme marker and the relative cell viability was calculated. The results are shown in Figure 2. Fig.12As shown in the figure, it can be seen that near-infrared irradiation or not will not change the trend that the viability of 4T1 cells decreases with the increase of sample working concentration, but in the range of 25-100 μg / ml, near-infrared light irradiation will significantly decrease the viability of 4T1 cells (p<0.05), and with the increase of concentration, this decrease further increases. Based on the results shown in Examples 8 and 9, the DOX&ICG@MgMnGa-LDHs nanotherapy system not only has photothermal properties, but also can accelerate the structural collapse of MgMnGa-LDHs under near-infrared light irradiation, prompting more DOX, ICG and Mn 3+ and Ga 3+ Ion release, this process enhances the killing effect of the above-mentioned active ingredients on tumor cells, forms a synergistic effect among chemotherapy, photothermal therapy and chemodynamic therapy, and ultimately achieves multimodal combined anti-tumor treatment.
Claims
1. A method for preparing a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system, characterized in that: The specific steps include: (1) dissolving a Mg source, a Mn source and a Ga source in the same ultrapure water to prepare a solution I; dissolving a strong base, a metal nitrate or a metal carbonate in the same ultrapure water to prepare a solution II; adding the solution I dropwise to the solution II under heating conditions, stirring evenly, to obtain a solution III; (2) reacting the solution III obtained in step (1) at a temperature of 20 to 50° C. for 8 to 20 hours with continuous stirring to obtain a suspension I; (3) centrifuging the suspension I obtained in step (2), then washing with ultrapure water, and drying under vacuum at room temperature to obtain a dark brown MgMnGa-LDHs product; (4) adding the MgMnGa-LDHs synthesized in step (3) to a phosphate buffer solution, and performing ultrasonic dispersion to obtain a suspension II; adding doxorubicin hydrochloride and indocyanine green to the phosphate buffer solution in sequence, and performing magnetic stirring to obtain a solution IV; (5) The suspension II and the solution IV are mixed and stirred evenly in the dark to obtain a solution V; the solution V is centrifuged, then washed with a phosphate buffer solution, and dried under vacuum at room temperature to obtain a dual-drug loaded ternary layered metal hydroxide nanotherapeutic system.
2. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: The amount of Mg source added to solution I of step (1) is 0.1-5 g per 50-200 mL of ultrapure water; the amount of Mn source added to solution I is 0.03-3 g per 50-200 mL of ultrapure water; the amount of Ga source added to solution I is 0.05 g-4 g per 50-200 mL of ultrapure water; the Mg source, Mn source, and Ga source are their corresponding metal chlorides or metal nitrates.
3. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: In step (1), the amount of strong base added to solution II is 0.1 to 15 g per 50 to 200 mL of ultrapure water; the strong base is NaOH or KOH; the amount of metal nitrate or metal carbonate in solution II is 0.2 to 25 g per 50 to 200 mL of ultrapure water, and the metal in the metal nitrate or metal carbonate is Na or K.
4. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: In step (1), the volume ratio of solution I to solution II is (0.6-1.5):
1.
5. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: In step (1), the heating temperature is 20-70° C., the dripping speed of solution I to solution II is 0.5-2 s / drop, and the stirring speed is 100-500 r / min.
6. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: The amount of MgMnGa-LDHs in suspension II of step (4) is 1 to 30 mg per 10 to 30 mL of phosphate buffer solution; the amount of doxorubicin hydrochloride in solution IV is 5 to 100 mg per 10 to 30 mL of phosphate buffer solution; and the amount of indocyanine green in solution IV is 5 to 100 mg per 10 to 30 mL of phosphate buffer solution.
7. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: In step (4), the concentration of the phosphate buffer solution is 0.1 mol / L, and the magnetic stirring time is 5 to 10 min.
8. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: In step (5), the volume ratio of suspension II to solution IV is 1:(0.6-1.5).
9. The method for preparing the dual-drug loaded ternary layered metal hydroxide nanotherapeutic system according to claim 1, characterized in that: The temperature for stirring in the dark in step (5) is 20-50° C., the time for stirring in the dark is 8-48 h, and the speed for stirring in the dark is 300-1000 r / min.
Citation Information
Patent Citations
Ultrathin CoMn-LDH (layered double hydroxide) composite photosensitizer and application thereof to tumor therapy and MRI (magnetic resonance imaging)
CN109432424A
Cobalt-manganese-iron hydrotalcite-based nano composite material as well as preparation method and application thereof
CN113274505A